Manual of engineering drawing : technical product specification and documentation to British and international standards - Simmons, C. H. (Butterworth Heinemann, 2012)
Now in its 4th edition, Manual of Engineering Drawing is a long-established guide for practicing and student engineers to producing engineering drawings and annotated 3D models that comply with the latest BSI and ISO standards of technical product specifications and documentation. This new edition has been updated in line with recent standard revisions and amendments, including the requirements of BS8888 2011 and related ISO standards. Ideal for international use, it includes a guide to the fundamental differences between the relevant ISO and ASME standards, as well as new information on legal aspects such as patents and copyright, and end-of-life design considerations.